Private Tutoring in Vietnam A Review of Current Issues and its Major Correlates - Dang, Hai-Anh H. (The World Bank, 2013)
Building on the earlier work, this paper provides an updated review of the private tutoring phenomenon in Vietnam in several aspects, including the reasons, scale, intensity, form, cost, and legality of these classes. In particular, the paper offers a comparative analysis of the trends in private tutoring between 1998 and 2006 where data are available. Several (micro-) correlates are examined that are found to be strongly correlated with student attendance at tutoring, including household income, household head education and residence area, student current grade level, ethnicity, and household size. In particular, the analysis focuses on the last three variables, which have received little attention in the previous literature on the determinants of tutoring